In‐situ and quantitative analysis of aged silicone rubber materials with laser‐induced breakdown spectroscopy. Issue 2 (1st June 2018) - Xilin, Wang; Xiao, Hong; Ping, Chen; Chenlong, Zhao; Zhidong, Jia; Liming, Wang; Qishen, Lv; Ronghui, Huang; Shungui, Liu
Abstract : Due to their weak weather ability, the ageing process of organic silicone rubber composites remarkably influences the service performance of composite insulators and bushings, especially in high‐voltage transmission lines. In this study, laser‐induced breakdown spectroscopy (LIBS) was used for analysing ageing composite insulator sheds for potential on‐site application. A spectrum was recorded after each laser pulse and the element composition of ablated materials with different depth was observed. A calibration curve that revealed linear relationship between C, Si, Al spectrum line intensity and corresponding element concentration was established with the result of X‐ray photoelectron spectroscopy test. Regularly line intensities of C, Si and Al changed dramatically from the surface to the bulk layer. Given the number of laser pulses with varying element concentrations, as well as the linear relationship described above, the depth of ageing layer could be calculated immediately. Also, the result was verified by secondary ion mass spectrometry and scanning electron microscope. LIBS method can be a promising and efficient technique to assess the ageing state of composite materials on site.